Authenticity of the “Interrogatio” Iohannis in the Light of Contemporary Deconstructionist Source Criticism - Czarnecki, Piotr (Studia Ceranea, 2023)
Scholars of Catharism representing the deconstructionist current in the recent years continue their struggle with the traditional interpretation of this heresy which underlines its dualistic character and strong connections with Eastern dualisms – especially with Bogomilism. Their tactics is focused primarily on questioning the authenticity of the sources confirming Cathar dualism and its Eastern roots. Such sources are presented as forgeries invented by the Catholics trying to discredit the “dissidents”. This tactic is directed primarily against the sources of heretical provenience, which are the strongest arguments against the deconstructionist interpretation. Previously, the deconstructionist scholars questioned the acts of the Cathar council in Saint-Felix-De-Caraman, and the so-called “Manichaean treatise” – a Cathar theological work aimed at proving ontological dualism based on the specific interpretation of numerous biblical passages. Currently the deconstructionists speak about the need for verification of another Cathar dualistic treatise – Liber De Duobus pricipiis. Considering this we may expect that soon also the Interrogatio Iohannis will be questioned, as it is a crucial source confirming both the dualism of the Cathars and their dependence on the Bogomils. Before it happens I decided to take a closer look at this apocryphal text. Through the analysis of its doctrine in the light of the Eastern sources concerning the Bogomils I am going to answer the question of whether this work, known only from the Latin manuscripts, indeed could have been created by the Bogomils and if it is possible to question its authenticity using the patterns used by the deconstructionist scholars.